2018
DOI: 10.1108/ijshe-09-2017-0168
|View full text |Cite
|
Sign up to set email alerts
|

Education for sustainable development in Portuguese universities

Abstract: Purpose This paper aims to determine, from key actors’ perspective, how sustainability has been integrated into the policies and strategies of higher education institutions (HEIs), particularly Portuguese public universities, within the framework of the United Nations Decade of Education for Sustainable Development (UN DESD) 2005-2014. Design/methodology/approach Semi-structured exploratory interviews were conducted after gathering a sample of 15 key actors in decision-making processes who designed and imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 33 publications
3
55
1
Order By: Relevance
“…In Portugal, HEIs do not yet prioritize implementing SD throughout the system and this must therefore be addressed (Aleixo et al, 2018b). Previous studies show a lack of national integrated strategies and policies, plans and programs on the integration of ESD into Portuguese HEI (Farinha et al, 2017) as well as an absence of a centralized system for implementing sustainable in HEIs (Farinha et al, 2018).…”
Section: The Portuguese Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…In Portugal, HEIs do not yet prioritize implementing SD throughout the system and this must therefore be addressed (Aleixo et al, 2018b). Previous studies show a lack of national integrated strategies and policies, plans and programs on the integration of ESD into Portuguese HEI (Farinha et al, 2017) as well as an absence of a centralized system for implementing sustainable in HEIs (Farinha et al, 2018).…”
Section: The Portuguese Scenariomentioning
confidence: 99%
“…Despite the lack of both government institutions' commitment to implement ESD in higher education and documents linked to SD, "Portuguese universities´ autonomy and their social responsibility have led them to develop several initiatives and policies toward ESD" (Farinha et al, 2018). Recent studies in Portugal (e.g., Aleixo et al, 2018a) showed that although Portuguese HEIs recognize the need to introduce sustainable competencies and topics in all courses, their vision of how to implement this differs.…”
Section: The Portuguese Scenariomentioning
confidence: 99%
“…Communication is a core function of higher education [9]. In terms of ESD coordination and communication at the national level, it should be mentioned that there is an existing gap arising from the lack of ESD at governmental policy and strategy levels either by the Portuguese Government or the Ministry of Public Universities [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In Portugal, earlier research showed that embedding sustainability (the "top-down" approach) is insufficiently developed in Portuguese governmental institutions at university level [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research studies were performed focusing on the sustainability in education and on the education for the continuous sustainable development at universities [40,41]. This research is focused on the identification of expectations and motivational factors of students at a university, specifically on the factors that can influence their decision-making on enrolling, successful studying, and finishing the studies at a university.…”
Section: Education and Sustainabilitymentioning
confidence: 99%